Fauna And Ecology Of Aquatic Organisms Common In Aquatic Ecosystems Of Southern Uzbekistan. (Texas Journal of Agriculture and Biological Sciences, 2024)
The study of the fauna and ecology of hydrobionts common in the aquatic ecosystems of Southern Uzbekistan is considered one of the urgent tasks. As a result of our research, it was established that 40 species are common in the Surkhandarya region, 25 species in coastal waters, 39 species in Kashkadarya and 26 species in coastal waters. Among the bivalve mollusks common in the rivers of Southern Uzbekistan, Corbiculla cor, Corbiculla fluminalis, Corbiculla purpurea, and among the fish, Pseudoscaphirhynchus kaufmanni, Pseudoscaphirhynchus hermanni, Capoetobrama kuschakewitschi, Luciobarbus capito, Sabanejewia aurata, Glyptosternum oschanini are listed in the "Red Book" of the Republic of Uzbekistan as rare species. When studying species depending on their habitat, it was found that 31 species are adapted to life in different environments, and 14 species are common in a constant (homogeneous) environment. It is evident that hydrobionts common in the aquatic ecosystems of Southern Uzbekistan are widely distributed in a variable habitat